Thermoplastic resin composition for electromagnetic wave absorber, and molded article

By using small-particle carbon nanotubes and carbon black in the resin composition, the problems of insufficient dispersion and angle dependence of carbon nanotubes in the resin composition are solved, and electromagnetic wave absorption performance with low reflection loss and transmission loss are achieved. in the millimeter wave band of the 60GHz to 90GHz frequency band.

CN119278239APending Publication Date: 2025-01-07아티엔스가부시키가이샤 +1

Patent Information

Application Number
CN202380043301.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-07-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When used for electromagnetic wave absorption, the reflection loss and transmission loss are insufficient, and the high aspect ratio of carbon nanotubes leads to insufficient dispersion, resulting in granular and orientation problems, which affect the appearance and electromagnetic wave absorption performance. Dependency.

Method used

Using a thermoplastic resin composition, including carbon nanotubes with an average diameter of 1 nm to 15 nm and carbon black with an average primary particle diameter of 20 nm to 50 nm, satisfies the specific melt flow rate and reflection/transmission attenuation conditions, and is used in combination. The carbon nanotubes and carbon black with particle size control the orientation of the carbon nanotubes in the molded body, and improve the dispersion and electromagnetic wave absorption performance.

Benefits of technology

The electromagnetic wave absorption performance with low reflection loss and transmission loss is achieved, and the angular dependence of electromagnetic wave absorption performance is reduced, and it is suitable for millimeter wave bands in specific frequency bands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156100840000191
    Figure BDA0005156100840000191
  • Figure BDA0005156100840000241
    Figure BDA0005156100840000241
  • Figure BDA0005156100840000251
    Figure BDA0005156100840000251
Patent Text Reader

Abstract

One embodiment of the present invention relates to a thermoplastic resin composition for electromagnetic wave absorbers, which contains a thermoplastic resin (A), carbon nanotubes (B) having an average diameter of 1-15 nm, and carbon black (C) having an average primary particle diameter of 20-50 nm, and satisfies any one of (i)-(iv), in which [Delta] RL represented by formula (1) is 3 dB or less, and [Delta] TL represented by formula (2) is 5 dB or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a thermoplastic resin composition for an electromagnetic wave absorber, and a molded article. Background Art

[0002] Plastics are used in a wide range of fields such as electrical and electronic equipment parts, automobile parts, medical parts, and food containers because they are easy to mold. In order to improve the decorativeness or to impart functionality, plastic molded products are being actively colored. In the automotive field in particular, molded products colored for electromagnetic wave absorption purposes are being circulated as a means of imparting functionality.

[0003] Electromagnetic waves are radiated from communication equipment such as radio, television, and wireless communication, but also from electronic devices such as mobile phones and personal computers, which have increased dramatically due to the recent progress in information technology. Conventionally, as a method for avoiding malfunctions caused by electromagnetic waves from electronic equipment, communication equipment, etc., an electromagnetic wave absorber that efficiently absorbs electromagnetic waves and converts the absorbed electromagnetic waves into heat energy is placed near or far from the electromagnetic wave generating site.

[0004] An example of using an electromagnetic wave absorber at a distance from the electromagnetic wave generating site is the use of an automatic toll collection system (ETC: electronic toll collection system) on highways. ETC is a system that uses microwaves with a frequency of 5.8 GHz between the roadside antenna and the vehicle-mounted antenna included in the toll station when a car passes through the toll station exit on the highway to exchange billing information, etc. In the toll station where the ETC system is introduced, the microwaves radiated from the antenna are reflected by the roof of the toll station, etc., and sometimes cause abnormalities in communication due to the leakage of unnecessary electromagnetic waves from the adjacent ETC channels. Therefore, communication abnormalities are suppressed by installing an electromagnetic wave absorber on the roof of the toll station or between the ETC channels.

[0005] Furthermore, in the automotive field in recent years, millimeter wave radars have been used for the purpose of autonomous driving of vehicles or collision prevention, and in many cases, millimeter wave radar devices are installed inside the vehicle.

[0006] Millimeter waves are electromagnetic waves with a wavelength of 1mm to 10mm and a frequency of 30GHz to 300GHz. They are currently used in vehicle-mounted radars, full-body scanners that see through clothes as a precautionary inspection at airports, and image transmission by surveillance cameras on platforms when a single person is driving a train. Millimeter-wave radar devices are devices that can receive waves that bounce back after skipping over millimeter waves and identify obstacles. Since they can detect a large distance or are not easily hindered by sunlight, rain, and fog, they are currently used in autonomous driving technologies for cars, etc. In the case of automotive sensors, millimeter-wave radar devices can send and receive millimeter waves from antennas and detect the relative distance or relative speed to obstacles.

[0007] The transmitting and receiving antennas of the millimeter wave radar device sometimes also receive reflections on the road surface other than the target obstacle, and sometimes the detection accuracy of the device is reduced. In order to solve this problem, in the millimeter wave radar device, an electromagnetic wave absorber is provided between the antenna and the control circuit as a shielding member for shielding electromagnetic waves.

[0008] As electromagnetic wave absorbing materials for the millimeter wave band constituting such electromagnetic wave absorbers, carbon-based, metallic carbon-based, and magnetic-based materials are known. In recent years, carbon nanotubes (CNTs) as carbon-based materials have attracted attention due to their high electrical conductivity and relatively light weight.

[0009] Resin compositions containing carbon nanotubes have high conductivity and are therefore used as parts requiring conductivity in the fields of automobiles, home appliances, and building components (Patent Document 1) or as electromagnetic wave absorbers that utilize electromagnetic wave characteristics (Patent Documents 2 and 3).

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2016-108524

[0013] Patent Document 2: Japanese Patent Publication No. 2017-512847

[0014] Patent Document 3: Japanese Patent Publication No. 2016-504471 Summary of the invention

[0015] Problems to be solved by the invention

[0016] However, molded articles using these conventional resin compositions cannot be said to have sufficient electromagnetic wave absorption performance for sufficiently protecting radar from the surrounding environment and not hindering radar signal transmission with respect to reflection loss and transmission loss of electromagnetic waves.

[0017] In addition, carbon nanotubes are materials with a relatively high aspect ratio and therefore difficult to disperse. If the dispersion is insufficient, particles or melt marks (wave-like patterns) may appear on the surface of the molded body, which may damage the appearance. Furthermore, carbon nanotubes tend to be oriented in a specific direction during molding, and the angle dependence of the electromagnetic wave absorption performance of the molded body varies depending on the incident angle of the electromagnetic wave.

[0018] As described above, it is difficult to achieve both high conductivity and dispersion stability of carbon nanotubes. Therefore, the object of the present invention is to provide a thermoplastic resin composition for an electromagnetic wave absorber having excellent dispersibility, and a molded body having excellent electromagnetic wave absorption performance with low reflection loss and transmission loss, and further having low angular dependence of electromagnetic wave absorption performance.

[0019] Among them, a molded body for a millimeter wave absorber having excellent reflection loss and transmission loss in a specific frequency band of 60 GHz to 90 GHz called millimeter waves is provided.

[0020] Technical means of solving problems

[0021] The present inventors have conducted diligent studies and, as a result, have found that the problems of the present invention can be solved in the following aspects, thereby completing the present invention.

[0022] That is, the present invention includes the following embodiments.

[0023] One embodiment relates to a thermoplastic resin composition for an electromagnetic wave absorber, comprising: a thermoplastic resin (A), carbon nanotubes (B) having an average diameter of 1 nm to 15 nm, and carbon black (C) having an average primary particle diameter of 20 nm to 50 nm, and

[0024] The thermoplastic resin composition for an electromagnetic wave absorber satisfies any one of the following (i) to (iv),

[0025] ΔRL represented by the following equation (1) is 3 dB or less, and ΔTL represented by the following equation (2) is 5 dB or less.

[0026] (i): The thermoplastic resin (A) includes a polyolefin resin (A1) having a melt mass-flow rate (MFR) of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf.

[0027] (ii): The thermoplastic resin (A) includes a polyamide resin (A2) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf.

[0028] (iii): The thermoplastic resin (A) contains a polyester resin (A3) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0029] (iv): The thermoplastic resin (A) includes a polycarbonate resin (A4) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0030] Formula (1) ΔRL=|RL(MD)-RL(TD) |

[0031] Formula (2) ΔTL=|TL(MD)-TL(TD) |

[0032] (In addition, RL (machine direction, MD) and RL (transverse direction, TD) are transmission attenuation values ​​obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, which is formed from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, with the electric field direction of the electromagnetic wave being parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction), respectively, after the molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm is left to stand for 1 day.)

[0033] In addition, TL(MD) and TL(TD) are the reflection attenuation amounts obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each of which is formed from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction) with respect to the thickness direction of the molded body after the molded body has been left to stand for 1 day.

[0034] In addition, the longitudinal direction of the molded body is the injection direction)

[0035] Another embodiment relates to a molded body formed from the thermoplastic resin composition for an electromagnetic wave absorber.

[0036] Effects of the Invention

[0037] The thermoplastic resin composition for an electromagnetic wave absorber of the present invention has excellent dispersibility, and the electromagnetic wave absorber obtained therefrom exhibits excellent electromagnetic wave absorption performance with low reflection loss and transmission loss, and further, the angle dependence of the electromagnetic wave absorption performance is small.

[0038] Among them, since the reflection loss and the transmission loss in the specific frequency band of 60 GHz to 90 GHz, which is called millimeter wave, are excellent, it can also be preferably used as a molded body for a millimeter wave absorber. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] [ Figure 1 ] Figure 1 This is a conceptual diagram of the measurement of the transmission attenuation and reflection attenuation of a millimeter wave transmitter.

[0040] [ Figure 2 ] Figure 2 This is a conceptual diagram of the measurement based on the incident angle dependence of the millimeter wave transmission device. DETAILED DESCRIPTION

[0041] Hereinafter, the present invention will be described in detail.

[0042] In addition, the numerical range specified using "to" in this specification is a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0043] In addition, carbon nanotubes are sometimes represented as CNT, and "carbon nanotubes (B) having an average diameter of 1 nm to 15 nm", "carbon black (C) having an average primary particle size of 20 nm to 50 nm", "polyolefin resin (A1) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230°C and a load of 2.16 kgf", "polyamide resin (A2) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240°C and a load of 2.16 kgf", ...carbon black (C) having an average primary particle size of 20 nm to 50 nm", "carbon black (A The polyester resin (A3) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf, the polycarbonate resin (A4) having an MFR of 5.0 g / 10 min to 50 g / 10 min, and the thermoplastic resin composition for electromagnetic wave absorber are referred to as “carbon nanotubes (B)”, “carbon black (C)”, “polyolefin resin (A1)”, “polyamide resin (A2)”, “polyester resin (A3)”, “polycarbonate resin (A4)”, and “thermoplastic resin composition”, respectively.

[0044] In addition, unless otherwise specified, various components appearing in the present specification may be used alone or in combination of two or more.

[0045] In addition, the numerical values ​​determined in this specification are values ​​obtained by the methods disclosed in the embodiments or examples.

[0046] The MFR in the embodiment of the present invention is a value obtained by measuring each thermoplastic resin as a value of melt mass flow rate in accordance with Japanese Industrial Standards (JIS) K7210.

[0047] 《Thermoplastic resin composition for electromagnetic wave absorber》

[0048] According to an embodiment of the present invention, a thermoplastic resin composition is used to form an electromagnetic wave absorber.

[0049] The thermoplastic resin composition comprises a thermoplastic resin (A), carbon nanotubes (B) having an average diameter of 1 nm to 15 nm, and carbon black (C) having an average primary particle diameter of 20 nm to 50 nm, and satisfies any one of the following (i) to (iv).

[0050] (i): The thermoplastic resin (A) contains a polyolefin resin (A1) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf.

[0051] (ii): The thermoplastic resin (A) includes a polyamide resin (A2) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf.

[0052] (iii): The thermoplastic resin (A) contains a polyester resin (A3) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0053] (iv): The thermoplastic resin (A) includes a polycarbonate resin (A4) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0054] In this way, by using carbon nanotubes having a small average diameter and carbon black having a small average primary particle size within a specific range, and combining these with a thermoplastic resin (A) satisfying any one of (i) to (iv), the orientation of the carbon nanotubes in the molded body can be controlled, and the carbon nanotubes in the thermoplastic resin composition have excellent stability, and the orientation when the molded body is formed can be suppressed.

[0055] In addition, ΔRL represented by the following equation (1) is 3 dB or less, and ΔTL represented by the following equation (2) is 5 dB or less.

[0056] Formula (1) ΔRL=|RL(MD)-RL(TD) |

[0057] Formula (2) ΔTL=|TL(MD)-TL(TD) |

[0058] (In addition, RL(MD) and RL(TD) are transmission attenuations obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each of which is molded from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction), with respect to the thickness direction of the molded body, after the molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm is left to stand for 1 day, and then the electromagnetic wave is incident on the molded body in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction) with respect to the thickness direction of the molded body,

[0059] In addition, TL(MD) and TL(TD) are the reflection attenuation amounts obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each of which is formed from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction) with respect to the thickness direction of the molded body after the molded body has been left to stand for 1 day.

[0060] In addition, the longitudinal direction of the molded body is the injection direction)

[0061] The injection direction referred to herein refers to the direction in which the thermoplastic resin composition flows from the gate portion of the molding machine into the mold.

[0062] That is, a molded body of 90 mm in length, 110 mm in width, and 3 mm in thickness means a molded body of 90 mm in length in the injection direction, 110 mm in length in a direction perpendicular to the injection direction, and 3 mm in thickness.

[0063] In addition, from the viewpoint of dispersibility and incident angle dependence, the total content of carbon nanotubes (B) and carbon black (C) is preferably 6% to 18% by mass, more preferably 6% to 15% by mass, and further preferably 8% to 13% by mass, based on the thermoplastic resin composition (100% by mass).

[0064] In the embodiment of the present invention, it is important not only to set ΔRL shown in formula (1) to 3 dB or less, and ΔTL shown in formula (2) to 5 dB or less, but also to use a thermoplastic resin (A) that satisfies any one of (i), (ii), (iii), or (iv) in combination with carbon nanotubes (B) having a small average diameter and carbon black (C) having a relatively small average primary particle size and a specific particle size range. In addition, the respective blending amounts are further reduced as much as possible and set to a specific range, thereby controlling the orientation of the carbon nanotubes and carbon black, and being able to exhibit sufficient electromagnetic wave absorption when electromagnetic waves are incident in a direction parallel to the injection direction of the molded body, not to mention the case where electromagnetic waves are incident in a direction perpendicular to the injection direction of the molded body, and further suppressing the angle dependence of the electromagnetic wave absorber.

[0065] <Thermoplastic resin (A)>

[0066] The thermoplastic resin (A) is a resin that can be molded by heating and melting, and the thermoplastic resin composition as an embodiment of the present invention satisfies any one of the following (i) to (iii).

[0067] (i): The thermoplastic resin (A) contains a polyolefin resin (A1) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf.

[0068] (ii): The thermoplastic resin (A) includes a polyamide resin (A2) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf.

[0069] (iii): The thermoplastic resin (A) contains a polyester resin (A3) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0070] (iv): The thermoplastic resin (A) includes a polycarbonate resin (A4) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0071] The polyolefin resin (A1), polyamide resin (A2), polyester resin (A3), or polycarbonate resin (A4) has high fluidity when melted. By selecting such a thermoplastic resin and using it in combination with carbon black (C) and carbon nanotubes (B), the orientation of the carbon nanotubes when forming a molded body can be suppressed, thereby obtaining a thermoplastic resin composition with a small angle dependence of electromagnetic wave absorption.

[0072] On the other hand, if the fluidity during melting is higher than a certain level, a surface layer with a relatively low concentration of carbon nanotubes (B) and a core layer with a relatively high concentration of carbon nanotubes (B) are generated on the surface and inside of the molded body, thereby generating a concentration gradient. Therefore, by selecting and using the thermoplastic resin, a molded body with a uniform carbon nanotube concentration can be obtained, thereby achieving an effect of reducing the angle dependence of electromagnetic wave absorption.

[0073] In addition, in each of the embodiments (i), (ii), (iii) or (iv), it is preferred to use a polyolefin resin (A1), a polyamide resin (A2), a polyester resin (A3), or a polycarbonate resin (A4) based on the thermoplastic resin (A), respectively, and it is preferred that at least any one of the polyolefin resin (A1), the polyamide resin (A2), the polyester resin (A3), and the polycarbonate resin (A4) is used as the main component.

[0074] The main component refers to a component having the highest content in the thermoplastic resin constituting the thermoplastic resin (A).

[0075] Specifically, in each embodiment, the content of the polyolefin resin (A1), the polyamide resin (A2), the polyester resin (A3), or the polycarbonate resin (A4) is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass, based on the thermoplastic resin (A).

[0076] [Polyolefin resin (A1)]

[0077] The polyolefin resin (A1) is a polyolefin resin having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf.

[0078] The polyolefin resin (A1) is a polymer containing olefins (monomers), and specifically, polyethylene resins (polyethylene, PE) such as high-density polyethylene (HDPE) or low-density polyethylene (LDPE), linear low-density polyethylene (linear low-density polyethylene (LLDPE)), polypropylene resins (poly propylene, PP), ethylene-α-olefin copolymers, ethylene-vinyl acetate copolymers, ethylene vinyl alcohol copolymers, ethylene ethyl acrylate copolymers, or cycloolefin polymers, cycloolefin copolymers and other cyclic olefin resins, etc. From the viewpoint of versatility or fluidity, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), or polypropylene resin (PP) are preferred. These polyolefin resins may also be oxidized polyolefins in which polyolefins are partially oxidized. In addition, the polyolefin resin (A1) may be used alone or in combination of two or more.

[0079] In addition, the polyolefin resin (A1) in the embodiment of the present invention has an MFR at a temperature of 230° C. and a load of 2.16 kgf in the range of 5.0 g / 10 min to 50 g / 10 min, preferably in the range of 15 g / 10 min to 40 g / 10 min, and particularly preferably in the range of 25 g / 10 min to 35 g / 10 min. In terms of incident angle dependency, it is preferably within the above range.

[0080] [Polyamide resin (A2)]

[0081] The polyamide resin (A2) is a polyamide resin having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf.

[0082] The polyamide resin (A2) is a polycondensate having an amide bond, and specific examples thereof include nylon 4,6, nylon 6, nylon 6,6, nylon 6,10, nylon 6,12, nylon 12, nylon 6,T, nylon 9,T, and aromatic nylon resins. In terms of versatility and fluidity, nylon 6 and nylon 6,6 are preferred. The polyamide resin (A2) may be used alone or in combination of two or more.

[0083] In addition, the polyamide resin (A2) in the embodiment of the present invention has an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf, preferably 15 g / 10 min to 40 g / 10 min, and particularly preferably 25 g / 10 min to 35 g / 10 min. In terms of the incident angle dependency, it is preferably within the above range.

[0084] [Polyester resin (A3)]

[0085] The polyester resin (A3) has an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280° C. and a load of 1.2 kgf.

[0086] The polyester resin (A3) is a polycondensate having an ester bond, and specific examples thereof include polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, and amorphous copolyester resin. In terms of versatility and fluidity, polyethylene terephthalate resin or polybutylene terephthalate resin is preferred. In addition, the polyester resin (A3) may be used alone or in combination of two or more.

[0087] In addition, the MFR of the polyester resin (A3) in the embodiment of the present invention at a temperature of 280° C. and a load of 1.2 kgf is in the range of 5.0 g / 10 min to 50 g / 10 min, preferably in the range of 15 g / 10 min to 40 g / 10 min, and particularly preferably in the range of 25 g / 10 min to 35 g / 10 min. In terms of the incident angle dependency, it is preferably within the above range.

[0088] [Polycarbonate resin (A4)]

[0089] The polycarbonate resin (A4) is a polycarbonate resin having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280° C. and a load of 1.2 kgf.

[0090] Polycarbonate resin (A4) is the polycondensate that the joint part of monomeric unit each other is carbonate group.Specifically, can use the resin that makes easily manufacture by making aromatic dihydroxy compound and carbonate precursor reaction such as phosgene or carbonic acid diester.As the manufacture of resin, for example, when using phosgene as carbonate precursor, can obtain by interfacial method, when using carbonic acid diester as carbonate precursor, can obtain by the transesterification method etc. of reacting in molten state.

[0091] In addition, the polycarbonate resin (A4) in the embodiment of the present invention has an MFR at a temperature of 280° C. and a load of 1.2 kgf in the range of 5.0 g / 10 min to 50 g / 10 min, preferably in the range of 15 g / 10 min to 40 g / 10 min, and particularly preferably in the range of 25 g / 10 min to 35 g / 10 min. In terms of the incident angle dependency, it is preferably within the above range.

[0092] From the viewpoint of electromagnetic wave absorption performance, the content of the thermoplastic resin (A) is preferably 82% by mass or more, more preferably 84% by mass or more, and further preferably 85% by mass or more, based on the thermoplastic resin composition (100% by mass). In addition, it is preferably 94% by mass or less, more preferably 92% by mass or less, and further preferably 90% by mass or less. The content of the thermoplastic resin (A) may be, for example, 82% by mass to 94% by mass, 84% by mass to 92% by mass, or 85% by mass to 90% by mass.

[0093] <Carbon nanotubes (B)>

[0094] The average diameter of the carbon nanotubes (B) determined by scanning electron microscopy is 1 nm to 15 nm, preferably 1 nm to 10 nm. Within this range, the carbon nanotubes in the thermoplastic resin composition have high dispersibility and the molded article has excellent electromagnetic wave absorption performance.

[0095] Specifically, for example, the average diameter of the carbon nanotubes is determined using a scanning electron microscope (e.g., JSM-6700M manufactured by JEOL Ltd.). The conditions are that the carbon nanotubes are observed at an accelerating voltage of 5 kV, and an image of 50,000 times (number of pixels: 1024×1280) is taken. Then, the minor axis lengths of 20 random carbon nanotubes in the taken image are measured, and the number average of these minor axis lengths is calculated as the average diameter of the carbon nanotubes.

[0096] The carbon nanotube (B) may be a single-layer carbon nanotube, a multi-layer carbon nanotube formed by winding two or more layers, or a mixture of these. In terms of cost and strength, multi-layer carbon nanotubes are preferred. In addition, carbon nanotubes having a non-graphite structure in the sidewalls of the carbon nanotubes may also be used.

[0097] Carbon nanotubes (B) can be generally produced by laser ablation, arc discharge, chemical vapor deposition (CVD), combustion, etc., and may be carbon nanotubes produced by any of the methods. In particular, the CVD method is generally a method in which catalyst particles containing a metal catalyst such as iron or nickel supported on a carrier such as silica, alumina, magnesia, titania, silicate, diatomaceous earth, alumina silica, silica titania, and zeolite are brought into contact with a carbon-containing gas as a raw material at a high temperature of 400°C to 1000°C, thereby producing carbon nanotubes inexpensively and in large quantities, and are also preferably used as carbon nanotubes in the embodiment of the present invention.

[0098] From the viewpoint of electromagnetic wave absorption performance, the content of carbon nanotubes (B) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more, based on the thermoplastic resin composition (100% by mass). In addition, it is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. The content of carbon nanotubes (B) may be, for example, 0.1% by mass to 5% by mass, 0.5% by mass to 5% by mass, 1% by mass to 3% by mass, or 1% by mass to 2% by mass.

[0099] <Carbon black (C)>

[0100] The average primary particle size of the carbon black (C) measured by a scanning electron microscope is 20 nm to 50 nm. Preferably, it is 25 nm or more. In addition, it is preferably 40 nm or less, and more preferably 35 nm or less. By using the carbon black (C) having an average primary particle size in the above range, after injection molding or extrusion molding, the carbon nanotubes (B) taken into the molded body can effectively form a conductive path with each other, and can stably show high conductivity and electromagnetic wave absorption performance.

[0101] Specifically, for example, the average primary particle size of carbon black is determined using a scanning electron microscope (e.g., JSM-6700M manufactured by JEOL Ltd.). The conditions are that the carbon black is observed at an accelerating voltage of 5 kV, and an image of 50,000 times (number of pixels: 1024×1280) is taken, and then the particle sizes of 20 random carbon blacks are measured in the taken image, and the number average is calculated as the average primary particle size of the carbon black.

[0102] In a thermoplastic resin composition in which only carbon nanotubes are formulated as a conductive material, when a molded body is manufactured by injection molding, it is difficult to show high conductivity even when the carbon nanotubes are fully dispersed in the composition. As a reason for this, it is believed that the factor is that a layer (so-called "surface layer") in which the presence ratio of the resin becomes high and the carbon nanotubes are at a low concentration is formed on the surface of the molded body. That is, in a thermoplastic resin composition, if a part in which the presence ratio of the resin is high and the carbon nanotubes are at a low concentration coexists with a part in which the presence ratio of the resin is low and the carbon nanotubes are at a high concentration, the viscosity (melt viscosity) when melted is different in each part, so that, for example, during extrusion molding, a part in which the presence ratio of the resin with low viscosity and high fluidity is high is extruded first during molding, and the surface of the molded body is covered by the surface layer, and it is estimated that the conductivity of the molded body is reduced.

[0103] On the other hand, carbon black generally has a lower specific surface area and oil absorption than carbon nanotubes, so the thermoplastic resin composition containing carbon black is less likely to have a higher melt viscosity than a thermoplastic resin composition containing only carbon nanotubes, and is less likely to form a surface layer on the surface of a molded body. In addition, carbon black also has good affinity with carbon nanotubes, so even if carbon nanotubes are taken into the molded body, a conductive path can be formed between the carbon black present on the surface of the molded body, so that the molded body as an embodiment of the present invention can show high conductivity.

[0104] That is, according to an embodiment of the present invention, in a thermoplastic resin composition, by using in combination carbon nanotubes (B) having a small average diameter and carbon black (C) having a relatively small average primary particle size within a specific range, the orientation of the carbon nanotubes and carbon black in the molded body is controlled, and sufficient electromagnetic wave absorption can be exhibited even when electromagnetic waves are incident in a direction parallel to the injection direction of the molded body, not to mention the case where electromagnetic waves are incident in a direction perpendicular to the injection direction of the molded body.

[0105] As carbon black (C), various carbon blacks may be used alone or in combination of two or more thereof: furnace black produced by continuous thermal decomposition of a gaseous or liquid raw material in a reaction furnace, especially Ketjen black produced by using ethylene heavy oil as a raw material, channel black produced by quenching and precipitating raw material gas by burning the raw material gas and contacting the bottom surface of the channel steel with its flame, thermal black produced by periodically and repeatedly burning and thermally decomposing a gas as a raw material, and especially acetylene black produced by using acetylene gas as a raw material, etc. In addition, carbon black produced by a conventional oxidation treatment or hollow carbon may also be used.

[0106] Examples of commercially available carbon black include furnace blacks such as Niteron #10, Niteron #200, and Niteron #300 manufactured by Nippon Steel Carbon Co., Ltd., furnace blacks such as Toka Black #4300, Toka Black #4400, Toka Black #4500, and Toka Black #5500 manufactured by Tokai Carbon Co., Ltd., furnace blacks such as Printex L manufactured by Degussa, Raven 7000, Raven 5750, Raven 5250, Raven 5000 ULTRA III, Raven 5000 ULTRA, Conductex SC ULTRA, Conductex 975 ULTRA, Puerto Rico ULTRA, and more. Columbian furnace blacks such as PUER BLACK 100, PUER BLACK 115, and PUER BLACK 205, Mitsubishi Chemical furnace blacks such as #30B, #45, #2350, #2400B, #2600B, #30050B, #3030B, #3230B, #3350B, #3400B, and #5400B, MONARCH 1400, MONARCH 1300, MONARCH 900, Vulcan XC-72R, and Black Pearl Black Pearls) 2000 and other furnace blacks manufactured by Cabot, Ensaco 250G, Ensaco 260G, Ensaco 350G and Super P-Li and other furnace blacks manufactured by Imerys, Ketjen Black EC-300J and Ketjen Black EC-600JD and other Ketjen Blacks manufactured by Akzo, DENKA BLACK HS-100, DENKA BLACK FX-35 and other acetylene blacks manufactured by Denki Kagaku Kogyo Co., Ltd., but are not limited to these.

[0107] From the viewpoint of electromagnetic wave absorption performance, the content of carbon black (C) is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 7% by mass or more, based on the thermoplastic resin composition (100% by mass). In addition, it is preferably 16% by mass or less, more preferably 15% by mass or less, and further preferably 12% by mass or less. The content of carbon black (C) may be, for example, 3% to 16% by mass, 5% to 15% by mass, or 7% to 12% by mass.

[0108] The content ratio (mass (%) / mass (%)) of carbon nanotubes (B) and carbon black (C) is preferably in the range of carbon nanotubes (B) / carbon black (C) = 1 / 2.5 to 1 / 20, more preferably in the range of 1 / 5 to 1 / 15.

[0109] <Other optional ingredients>

[0110] The thermoplastic resin composition may contain other optional components such as an electromagnetic wave absorber, a weathering stabilizer, an antistatic agent, a dye, a pigment, a coupling agent, a crystal nucleating agent, and a resin filler as required.

[0111] Furthermore, the thermoplastic resin composition preferably contains no volatile components.

[0112] In 100% by mass of the thermoplastic resin composition, the volatile components such as the solvent and the low-molecular-weight components are preferably 5% by mass or less, more preferably 1% by mass or less.

[0113] The electromagnetic wave absorbing material may include carbon nanotubes (B) and carbon nanotubes or carbon black other than carbon black (C) within a range not impairing the effects of the present invention. However, in terms of electromagnetic wave absorbing performance, the more carbon nanotubes (B) and carbon black (C) are contained in 100% by mass of the electromagnetic wave absorbing material, the more preferably, 50% to 100% by mass is more preferred, 70% to 100% by mass is further preferred, and 90% to 100% by mass is particularly preferred.

[0114] The content of the electromagnetic wave absorbing material other than the carbon nanotubes (B) and the carbon black (C) in 100% by mass of the electromagnetic wave absorbing material is preferably 10% by mass or less, more preferably 5% by mass or less.

[0115] If the dispersion of carbon nanotubes is poor, a high addition amount is required to achieve electromagnetic wave absorption performance within a practical range. However, although the transmission loss performance is improved due to high addition, electromagnetic waves are reflected, so the electromagnetic wave absorption performance is reduced.

[0116] In addition, when the electromagnetic wave absorption performance is to be achieved by using carbon black whose conductivity is inferior to that of carbon nanotubes, it is necessary to add more than carbon nanotubes. These electromagnetic wave absorption materials are in high concentration in the resin composition, thereby reducing the fluidity of the resin composition, and sometimes it is impossible to obtain uniform electromagnetic wave absorption performance in the molded product due to poor distribution.

[0117] However, in an embodiment of the present invention, the thermoplastic resin composition uses a combination of carbon nanotubes (B) having an average diameter of 1 nm to 15 nm and carbon black (C) having an average primary particle size of 20 nm to 50 nm, and thus has a specific relationship between reflection attenuation and transmission attenuation. Therefore, even if the electromagnetic wave absorbing material is not added in a high amount, the molded body can achieve high electromagnetic wave absorption performance and suppression of angle dependence.

[0118] <Method for producing thermoplastic resin composition>

[0119] The method for producing the thermoplastic resin composition according to the embodiment of the present invention is not particularly limited.

[0120] For example, a thermoplastic resin (A), carbon nanotubes (B), carbon black (C), and optionally additives are added and mixed using a Henschel mixer, a tumbler, a disperser, or the like, and mixed or melt-kneaded using a kneader, a roll mill, a super mixer, a Henschel mixer, a Schugi mixer, a vertical granulator, a high-speed mixer, a Pharmatrix mixer, a ball mill, a steel mill, a sand mill, a vibration mill, an attritor, a batch mixer such as an internal mixer, a twin-screw extruder, a single-screw extruder, a rotor-type twin-screw mixer, or the like, to obtain a resin composition in the form of pellets, powder, granules, or beads.

[0121] In the embodiment of the present invention, it is preferred to use a twin-screw extruder for melt kneading.

[0122] In the embodiment of the present invention, the thermoplastic resin composition may be a masterbatch containing carbon nanotubes (B) and carbon black (C) at a relatively high concentration and diluted with a thermoplastic resin (A) for use during molding, or may be a mixture containing carbon nanotubes (B) and carbon black (C) at a relatively low concentration and not diluted with a thermoplastic resin (A) and provided for molding with the original composition. In terms of the addition cost and inventory cost, a masterbatch that can be highly concentrated is preferred. The masterbatch is preferably in a pellet form that is easy to handle.

[0123] "Formed Body"

[0124] The molded article is formed from the thermoplastic resin composition according to the embodiment of the present invention and is used for an electromagnetic wave absorber.

[0125] The molded article can be obtained by melt-mixing a mixture or a masterbatch as a thermoplastic resin composition with a diluted resin in a molding machine usually set at 50° C. to 350° C., forming the molded article into a shape, and cooling. The temperature of the molding machine has no problem as long as it is a temperature at which the thermoplastic resin (A) softens, but is a temperature 30° C. or higher than the softening point of the thermoplastic resin as the main component.

[0126] The shape of the molded body is preferably a plate, a rod, a fiber, a tube, a pipe, a bottle, a film, or the like.

[0127] As the molding method, for example, extrusion molding, injection molding, blow molding, compression molding, transfer molding, film molding such as T-die molding or blow molding, calendar molding, spinning, etc. can be used.

[0128] According to an embodiment of the present invention, the thermoplastic resin composition can highly control the orientation of carbon nanotubes (B), so even an injection-molded body or an extruded body that is prone to orientation can exhibit excellent effects in terms of high electromagnetic wave absorption performance and suppression of angle dependence.

[0129] From the viewpoint of electromagnetic wave absorption performance, the content of carbon nanotubes (B) in the molded body is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more, based on the thermoplastic resin composition (100% by mass). In addition, it is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. The content of carbon nanotubes (B) may be, for example, 0.1% by mass to 5% by mass, 0.5% by mass to 5% by mass, 1% by mass to 3% by mass, or 1% by mass to 2% by mass.

[0130] In addition, from the viewpoint of electromagnetic wave absorption performance, the content of carbon black (C) in the molded body is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 7% by mass or more, based on the thermoplastic resin composition (100% by mass). In addition, it is preferably 16% by mass or less, more preferably 15% by mass or less, and further preferably 12% by mass or less. The content of carbon black (C) may be, for example, 3% to 16% by mass, 5% to 15% by mass, or 7% to 12% by mass.

[0131] Electromagnetic wave absorbers convert the energy of incident electromagnetic waves into heat energy and absorb it inside the absorber. Unlike electromagnetic wave shielding materials, the purpose of electromagnetic wave absorbers is to absorb electromagnetic waves inside the molded body rather than reflect them on the surface of the molded body.

[0132] Electromagnetic wave absorbers are used in automatic toll collection systems (ETC) on highways, vehicle-mounted radars, full-body scanners that see through clothes as a preventive check at airports, etc., millimeter-wave radar devices used in image transmission for surveillance cameras on platforms when a train is operated by a single person, and radar artifact prevention on ship masts.

[0133] Among them, the molded article formed from the thermoplastic resin composition according to the embodiment of the present invention is excellent in electromagnetic wave absorption performance in the millimeter wave band of 60 GHz to 90 GHz, and therefore can also be preferably used in millimeter wave radar devices.

[0134] Examples of embodiments of the present invention are given below. The present invention is not limited to the following.

[0135] [1] A thermoplastic resin composition for an electromagnetic wave absorber, comprising: a thermoplastic resin (A), carbon nanotubes (B) having an average diameter of 1 nm to 15 nm, and carbon black (C) having an average primary particle diameter of 20 nm to 50 nm, and

[0136] The thermoplastic resin composition for an electromagnetic wave absorber satisfies any one of the following (i) to (iv),

[0137] ΔRL represented by the following equation (1) is 3 dB or less, and ΔTL represented by the following equation (2) is 5 dB or less.

[0138] (i): The thermoplastic resin (A) contains a polyolefin resin (A1) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf.

[0139] (ii): The thermoplastic resin (A) includes a polyamide resin (A2) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf.

[0140] (iii): The thermoplastic resin (A) contains a polyester resin (A3) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0141] (iv): The thermoplastic resin (A) includes a polycarbonate resin (A4) having an MFR of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280°C and a load of 1.2 kgf.

[0142] Formula (1) ΔRL=|RL(MD)-RL(TD) |

[0143] Formula (2) ΔTL=|TL(MD)-TL(TD) |

[0144] (In addition, RL(MD) and RL(TD) are transmission attenuations obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each of which is molded from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction), with respect to the thickness direction of the molded body, after the molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm is left to stand for 1 day, and then the electromagnetic wave is incident on the molded body in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction) with respect to the thickness direction of the molded body,

[0145] In addition, TL(MD) and TL(TD) are the reflection attenuation amounts obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each of which is formed from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, in a direction parallel to the injection direction (MD direction) or perpendicular to the injection direction (TD direction) with respect to the thickness direction of the molded body after the molded body has been left to stand for 1 day.

[0146] In addition, the longitudinal direction of the molded body is the injection direction)

[0147] [2] The thermoplastic resin composition for an electromagnetic wave absorber according to [1], wherein the total content of the carbon nanotubes (B) and the carbon black (C) is 6% to 18% by mass based on the thermoplastic resin composition for an electromagnetic wave absorber. For example, the total content of the carbon nanotubes (B) and the carbon black (C) may be 6% to 15% by mass.

[0148] [3] The thermoplastic resin composition for an electromagnetic wave absorber according to [1] or [2], wherein the content of the thermoplastic resin (A) is 82% to 94% by mass based on the thermoplastic resin composition for an electromagnetic wave absorber. For example, the content of the thermoplastic resin (A) may be 85% to 90% by mass.

[0149] [4] The thermoplastic resin composition for an electromagnetic wave absorber according to any one of [1] to [3], wherein the content of the thermoplastic resin (A) is 82% to 94% by mass, the content of the carbon nanotubes (B) is 1% to 3% by mass, and the content of the carbon black (C) is 5% to 15% by mass, based on the thermoplastic resin composition for an electromagnetic wave absorber. For example, the content of the thermoplastic resin (A) may be 85% to 90% by mass, the content of the carbon nanotubes (B) may be 1% to 3% by mass, and the content of the carbon black (C) may be 5% to 12% by mass.

[0150] [5] A molded article formed from the thermoplastic resin composition for an electromagnetic wave absorber according to any one of [1] to [4].

[0151] The disclosure of this application is related to the subject matter described in Japanese Patent Application No. 2022-124303 filed on August 3, 2022, and all the disclosed contents are incorporated herein by reference.

[0152] Example

[0153] Hereinafter, the present invention will be described in more detail by way of examples, but the following examples do not limit the present invention in any way. In addition, the "parts" in the examples represent "parts by mass" and the "%" represents "mass %". In addition, the amounts in the tables are mass %, and the blanks in the tables represent that no amount is added.

[0154] In addition, the average diameter of carbon nanotubes, the average primary particle size of carbon black, and the MFR of the thermoplastic resin (A) were measured by the following method.

[0155] <Average diameter of carbon nanotubes>

[0156] The carbon nanotubes were observed using a scanning electron microscope (JSM-6700M manufactured by JEOL Ltd.) at an accelerating voltage of 5 kV, and an image at 50,000 times magnification (number of pixels: 1024×1280) was taken. Next, the minor axis lengths of 20 random carbon nanotubes in the taken image were measured, and the number average of these minor axis lengths was taken as the average diameter of the carbon nanotubes.

[0157] <Average primary particle size of carbon black>

[0158] A scanning electron microscope (manufactured by JEOL, JSM-6700M) was used to observe carbon black at an accelerating voltage of 5 kV, and an image of 50,000 times (number of pixels: 1024×1280) was taken. Next, the particle size of each of 20 random carbon blacks in the taken image was measured, and the number average was taken as the average primary particle size of the carbon black.

[0159] <MFR (melt mass flow rate) of thermoplastic resin (A)>

[0160] The MFR of the thermoplastic resin (A) is measured using a melt indexer manufactured by Toyo Seiki Co., Ltd. in accordance with JIS.K7210.

[0161] Regarding the measurement, for polyolefin resins, the measurement was carried out at a temperature of 230°C and a load of 2.16 kgf, for polyamide resins, the measurement was carried out at a temperature of 240°C and a load of 2.16 kgf, for polyester resins, the measurement was carried out at a temperature of 280°C and a load of 1.2 kgf, and for polycarbonate resins, the measurement was carried out at a temperature of 280°C and a load of 1.2 kgf.

[0162] The materials used in the examples are as follows.

[0163] <Thermoplastic resin (A)>

[0164] (A1-1) Prime Polypro J107G (polypropylene resin manufactured by Prime Polymer)

[0165] (A1-2) Prime Polypro J106G (polypropylene resin manufactured by Prime Polymer)

[0166] (A1-3) SunAllomer PM802A (polypropylene resin manufactured by SunAllomer)

[0167] (A2-4) Amilan CM1017 (nylon 6 manufactured by Toray Industries)

[0168] (A3-5) Duranex 700FP (polybutylene terephthalate resin manufactured by Polyplastics)

[0169] (A4-6) Iupilon H3000 (polycarbonate resin manufactured by Mitsubishi Engineering Plastics)

[0170] (A5-7) SunAllomer PMB60A (polypropylene resin manufactured by SunAllomer)

[0171] (A5-8) SunAllomer PM472W (polypropylene resin manufactured by SunAllomer)

[0172] (A5-9) Crystalline polyamide resin (MFR at 240°C x 1.2 kgf is 0.1 g / 10 min or less, MFR at 300°C x 10 kgf is 60 g / 10 min)

[0173] Table 1 summarizes the MFR of the thermoplastic resin (A) under various conditions.

[0174] [Table 1]

[0175] Table 1.

[0176]

[0177] <Carbon nanotubes (B), etc.>

[0178] (B-1) Flotube 7000 (manufactured by CNano, average diameter 6.0 nm)

[0179] (B-2) SMW210 (manufactured by SouthWest NanoTechnologies, average diameter 9.0 nm)

[0180] (B-3) CM-130 (manufactured by Hanwha Chemical Hanos, average diameter: 15.0 nm)

[0181] (B'-1) NTP3121 (manufactured by NTP, average diameter 30.0 nm)

[0182] <Carbon black (C), etc.>

[0183] (C-1) Mitsubishi Carbon #30B (manufactured by Mitsubishi Chemical Corporation, average primary particle size: 30 nm)

[0184] (C-2) Nylon #10 (furnace black manufactured by Nippon Steel Carbon Co., Ltd., average primary particle size 39 nm)

[0185] (C-3) Ensaco 250G (furnace black manufactured by Imerys, with an average primary particle size of 45 nm)

[0186] (C'-1) Mitsubishi Carbon #3030B (manufactured by Mitsubishi Chemical Corporation, average primary particle size 55 nm)

[0187] (C'-2) Mitsubishi Carbon #900B (manufactured by Mitsubishi Chemical Corporation, average primary particle size 16 nm)

[0188] (Manufacture of thermoplastic resin composition)

[0189] (Example 1)

[0190] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A1-1), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 230°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0191] (Example 2 to Example 14)

[0192] A thermoplastic resin composition was obtained by the same method as in Example 1 except that the materials and blending amounts (mass %) were changed to those shown in Table 2 and Table 3, respectively.

[0193] (Example 15)

[0194] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A2-4), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 280°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0195] (Example 16)

[0196] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A3-5), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 260°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0197] (Example 17)

[0198] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A4-6), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 280°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0199] (Comparative Example 1)

[0200] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A5-7), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 230°C using a single-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0201] (Comparative Example 2, Comparative Example 4 to Comparative Example 10)

[0202] A thermoplastic resin composition was obtained by the same method as in Comparative Example 1 except that the materials and blending amounts (mass %) were changed to those shown in Tables 3 and 4, respectively.

[0203] (Comparative Example 3)

[0204] A thermoplastic resin composition was obtained by mixing and melt-kneading 89% by mass of a thermoplastic resin (A5-9), 1% by mass of carbon nanotubes (B-1) and 10% by mass of carbon black (C-1), extruding and pelletizing at 280°C using a single-screw extruder (manufactured by The Japan Steel Works, Ltd.).

[0205] 《Physical properties and evaluation of thermoplastic resin compositions》

[0206] The physical property values ​​and evaluation results of the obtained thermoplastic resin composition were obtained by the following methods.

[0207] <Measurement of transmission attenuation and reflection attenuation>

[0208] The thermoplastic resin compositions obtained by Examples 1 to 14 and Comparative Examples 1 to 13 were injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with a cylinder setting temperature of 220°C and a mold temperature of 40°C to produce a molded body with a length (injection direction) of 90 mm, a width (direction perpendicular to the injection direction) of 110 mm, and a thickness of 3 mm.

[0209] The thermoplastic resin composition obtained by Example 15 and Example 17 was injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with a cylinder setting temperature of 280°C and a mold temperature of 80°C to produce a molded body with a length (injection direction) of 90 mm, a width (direction perpendicular to the injection direction) of 110 mm, and a thickness of 3 mm.

[0210] The thermoplastic resin composition obtained in Example 16 was injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with a cylinder setting temperature of 260°C and a mold temperature of 40°C to produce a molded body with a length (injection direction) of 90 mm, a width (direction perpendicular to the injection direction) of 110 mm, and a thickness of 3 mm.

[0211] In addition, the longitudinal direction of the molded body is the injection direction.

[0212] Using the obtained molded body, the reflection attenuation RL (TD) and the transmission attenuation TL (TD) of the electromagnetic wave in the direction of the electric field parallel to the injection direction of the molded body (MD direction) and perpendicular to the injection direction (TD direction) are measured by the following method.

[0213] Figure 1 When electromagnetic waves are incident on the thickness direction of the formed body, that is, when the plane of the formed body is placed still in the emission direction of the electromagnetic waves, the irradiation direction of the electromagnetic waves is (x), the direction of the electric field is (y), and the direction of the magnetic field is (z), 1. is the transmission attenuation TL (MD), 2. is the reflection attenuation RL (MD), 3. is the transmission attenuation RL (TD), and 4. is the measurement conceptual diagram of the reflection attenuation RL (TD).

[0214] like Figure 1As shown in 1. and 2., after the obtained molded body is left to stand for 1 day, the reflection attenuation RL (MD) and the transmission attenuation TL (MD) are measured when the electric field direction of the electromagnetic wave (y direction in the figure) is parallel to the emission direction (MD direction).

[0215] In addition, if Figure 1 As shown in 3. and 4., after the obtained molded body is left to stand for 1 day, the reflection attenuation RL (TD) and the transmission attenuation TL (TD) are measured when the electric field direction of the electromagnetic wave (y direction in the figure) becomes a direction (TD direction) perpendicular to the emission direction of the electric field direction of the electromagnetic wave (y direction in the figure).

[0216] Using E8257D+E8257DS12 (output: 4dBm) as a millimeter wave transmitting device, N9030A+M1970V as a millimeter wave receiving device, and AAHR015 (WR15, AET, INC) as a horn antenna (all manufactured by Keysight technologies), the reflection attenuation and transmission attenuation of the obtained molded body at a measuring frequency of 76.5 GHz were measured in an environment of temperature 24.8°C and relative humidity 48%.

[0217] Based on the obtained reflection attenuation amounts RL(MD), RL(TD), and transmission attenuation amounts TL(MD), TL(TD), the incident angle dependence ΔRL of the reflection attenuation and the incident angle dependence ΔTL of the transmission attenuation are calculated according to the following equations (1) and (2).

[0218] Formula (1) ΔRL=|RL(MD)-RL(TD) |

[0219] Formula (2) ΔTL=|TL(MD)-TL(TD) |

[0220] <Dispersibility>

[0221] The obtained thermoplastic resin composition for electromagnetic wave absorber was extruded by a T-type molding machine (manufactured by Toyo Seiki Co., Ltd.) with a cylinder setting temperature of 220°C and a mold temperature of 40°C to prepare a T-type film of 10 cm in width×5 m in length×100 μm in thickness.

[0222] The obtained T-type film was observed with an optical microscope (manufactured by KEYENCE), and the number of particles of 100 μm or more was counted, and the dispersibility was evaluated according to the following criteria.

[0223] [Evaluation criteria]

[0224] ○ (Good): The number of particles is less than 30

[0225] △(Practical): The number of particles is more than 30 and less than 50

[0226] × (Not applicable): The number of particles is 50 or more

[0227] <Electromagnetic wave absorption performance>

[0228] (Reflection loss RL(MD))

[0229] As an index of electromagnetic wave absorption performance, the reflection loss (dB) in the millimeter wave band was measured by the following method.

[0230] Using E8257D+E8257DS12 (output: 4dBm) as a millimeter wave transmitting device, N9030A+M1970V as a millimeter wave receiving device, and AAHR015 (WR15, AET, INC) as a horn antenna (all manufactured by Keysight technologies), at a temperature of 24.8°C and a relative humidity of 48%, the reflection loss of the molded bodies obtained in the embodiments and comparative examples was measured in a state where the emission direction (MD direction) at a measuring frequency of 76.5 GHz and the electric field direction of the electromagnetic wave (y direction in the figure) were parallel.

[0231] As the electromagnetic wave absorption performance, the reflection loss RL (MD) was evaluated according to the following criteria.

[0232] [Evaluation criteria]

[0233] ○(Good): Reflection loss is less than -6dB

[0234] △(Practical): Reflection loss is above -6dB and less than -5dB

[0235] ×(Not practical): Reflection loss is -5dB or more

[0236] (Transmission loss TL(MD))

[0237] As an index of electromagnetic wave absorption performance, the transmission loss (dB) in the millimeter wave band was measured by the following method.

[0238] Using E8257D+E8257DS12 (output: 4dBm) as a millimeter wave transmitting device, N9030A+M1970V as a millimeter wave receiving device, and AAHR015 (WR15, AET, INC) as a horn antenna (all manufactured by Keysight technologies), at a temperature of 24.8°C and a relative humidity of 48%, the transmission loss of the formed bodies obtained in the embodiments and comparative examples was measured in a state where the emission direction (MD direction) at a measuring frequency of 76.5 GHz and the electric field direction of the electromagnetic wave (y direction in the figure) were parallel.

[0239] The transmission loss TL (MD) was evaluated as the electromagnetic wave absorption performance according to the following criteria.

[0240] [Evaluation criteria]

[0241] ○(Good): Transmission loss is less than -15dB

[0242] △(Practical): Transmission loss is above -15dB and less than -10dB

[0243] ×(Not practical): Transmission loss is -10dB or more

[0244] <Incident angle dependence>

[0245] The angle dependency was evaluated using the incident angle dependency by the following method.

[0246] Using E8257D+E8257DS12 (output: 4dBm) as a millimeter wave transmitting device, N9030A+M1970V as a millimeter wave receiving device, and AAHR015 (WR15, AET, INC) as a horn antenna (all manufactured by Keysight technologies), at a temperature of 24.8°C and a relative humidity of 48%, the reflection loss and transmission loss of the molded bodies obtained in the embodiments and comparative examples were measured in a state where the emission direction (MD direction) at a measuring frequency of 76.5 GHz and the electric field direction of the electromagnetic wave (y direction in the figure) were parallel.

[0247] In this measurement, the molded body was set at an angle of 20° with respect to the irradiation direction of the electromagnetic wave, and the measurement was performed ( Figure 2 This is a conceptual diagram taking the measurement of transmission loss as an example).

[0248] The reflection loss RL (MD) was evaluated as the incident angle dependency based on the following criteria.

[0249] [Evaluation criteria]

[0250] ○(Good): Reflection loss is less than -5dB

[0251] △(Practical): Reflection loss is above -5dB and less than -3dB

[0252] ×(Not practical): Reflection loss is -3dB or more

[0253] In addition, the transmission loss TL (MD) was evaluated as the incident angle dependency according to the following criteria.

[0254] [Evaluation criteria]

[0255] ○(Good): Transmission loss is less than -15dB

[0256] △(Practical): Transmission loss is above -15dB and less than -10dB

[0257] ×(Not practical): Transmission loss is -10dB or more

[0258] [Table 2]

[0259] Table 2.

[0260]

[0261] [Table 3]

[0262] Table 3.

[0263]

[0264] [Table 4]

[0265] Table 4.

[0266]

[0267] In addition, for the thermoplastic resins of Examples 2 to 12, the thermoplastic resin compositions formed by replacing the thermoplastic resin (A1-1) with the thermoplastic resin (A2-4), the thermoplastic resin (A3-5), and the thermoplastic resin (A4-6), respectively, had the same evaluation results as when the thermoplastic resin (A1-1) was used.

[0268] That is, the effects were confirmed in all the forms (i) to (iv).

[0269] According to the evaluation results, in the thermoplastic resin composition according to the embodiment of the present invention and the molded body using the composition, the dispersibility of the resin composition is excellent, the molded body shows excellent electromagnetic wave absorption performance with low reflection loss and transmission loss, and even when the electromagnetic wave is incident at a changed incident angle, the electromagnetic wave absorption performance can be stably exhibited, thereby confirming excellent results in suppressing the angle dependence.

[0270] Among them, since the reflection loss and the transmission loss in the specific frequency band of 60 GHz to 90 GHz, which is called millimeter wave, are excellent, it can be said that it can also be preferably used as a molded body for a millimeter wave absorber.

Claims

1. A thermoplastic resin composition for an electromagnetic wave absorber, comprising: a thermoplastic resin (A), carbon nanotubes (B) having an average diameter of 1 nm to 15 nm, and carbon black (C) having an average primary particle size of 20 nm to 50 nm, and The thermoplastic resin composition for an electromagnetic wave absorber satisfies any one of the following (i) to (iv), ΔRL represented by the following equation (1) is 3 dB or less, and ΔTL represented by the following equation (2) is 5 dB or less, (i): The thermoplastic resin (A) comprises a polyolefin resin (A1) having a melt flow rate of 5.0 g / 10 min to 50 g / 10 min at a temperature of 230° C. and a load of 2.16 kgf, (ii): The thermoplastic resin (A) comprises a polyamide resin (A2) having a melt flow rate of 5.0 g / 10 min to 50 g / 10 min at a temperature of 240° C. and a load of 2.16 kgf, (iii): The thermoplastic resin (A) comprises a polyester resin (A3) having a melt flow rate of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280° C. and a load of 1.2 kgf, (iv): The thermoplastic resin (A) comprises a polycarbonate resin (A4) having a melt flow rate of 5.0 g / 10 min to 50 g / 10 min at a temperature of 280° C. and a load of 1.2 kgf, Formula (1) ΔRL = |RL (longitudinal) - RL (lateral) | Formula (2) ΔTL = |TL (longitudinal) - TL (transverse) | (In addition, RL (longitudinal direction) and RL (lateral direction) are transmission attenuation values ​​obtained when an electromagnetic wave with a frequency of 76.5 GHz is incident on a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, which is formed from a thermoplastic resin composition for an electromagnetic wave absorber by an injection molding machine, with the electric field direction of the electromagnetic wave being parallel to the injection direction (longitudinal direction) or perpendicular to the injection direction (lateral direction) with respect to the thickness direction of the molded body after the molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm is left to stand for 1 day, respectively, and then, In addition, TL (longitudinal direction) and TL (transverse direction) are the reflection attenuation amounts when a molded body having a length of 90 mm, a width of 110 mm, and a thickness of 3 mm, each molded from a thermoplastic resin composition for an electromagnetic wave absorber, is left to stand for 1 day, and an electromagnetic wave having a frequency of 76.5 GHz is incident in a direction parallel to the injection direction (longitudinal direction) or in a direction perpendicular to the injection direction (transverse direction) with respect to the thickness direction of the molded body, In addition, the longitudinal direction of the molded body is the injection direction).

2. The thermoplastic resin composition for an electromagnetic wave absorber according to claim 1, wherein The total content of the carbon nanotubes (B) and the carbon black (C) is 6% by mass to 18% by mass based on the thermoplastic resin composition for an electromagnetic wave absorber.

3. The thermoplastic resin composition for an electromagnetic wave absorber according to claim 1 or 2, wherein: Based on the thermoplastic resin composition for electromagnetic wave absorber, the content of thermoplastic resin (A) is 82% to 94% by mass, the content of carbon nanotubes (B) is 1% to 3% by mass, and the content of carbon black (C) is 5% to 15% by mass. 4 . A molded body formed from the thermoplastic resin composition for an electromagnetic wave absorber according to claim 1 .

Citation Information

Patent Citations

  • Conductive resin composition, conductive master batch, molded body, and production method of the same

    JP2016108524A

  • Thermoplastic resin composition for radar cover

    JP2016504471A

  • Composite materials with improved mechanical properties and molded articles containing them

    JP2017512847A

  • Soundproof box of work machine

    JP2022124303A

Cited By

  • High-frequency wave-absorbing material as well as preparation method and application thereof

    CN121495344A

  • High-frequency absorbing materials, their preparation methods and applications

    CN121495344B